Modal Sosial Komunitas KOPSRI (Kesatuan Organisasi Pencak Silat Rejosari) Dalam Pelestarian Kesenian Tradisional Bantengan Sebagai Budaya Lokal - Fadillah Sauma Ramadani (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
Traditional art is a type of local knowledge that is very important for maintaining the cultural identity of a community. In an increasingly modern and global world, traditional art is threatened with extinction because the younger generation is not interested and there are few initiatives to preserve it. Bantengan art is one of the traditional art styles that is still alive and developing in Indonesia, especially in Ngantang District, Malang Regency. Bantengan art today has been modified a lot in accordance with technological advances. This shows that Bantengan art can also be affected by the current of modernization. This study aims to understand the internal and external dynamics of the KOPSRI Community in its efforts to preserve Bantengan art, identify the challenges faced by the KOPSRI Community in preserving Bantengan art both in terms of regeneration, finance, and cultural competition, and analyze the strategies implemented by the KOPSRI Community in overcoming challenges and maintaining Bantengan art. This study uses James Coleman's social capital theory which emphasizes the key role of relational resources in determining social outcomes and provides insights into community cooperation and effectiveness. Social capital enables individuals or groups to achieve certain goals. This study uses a qualitative research method with an ethnographic approach. The informant determination method used purposive sampling. The results of this study indicate that the KOPSRI community has strong social capital that includes aspects of trust, social networks, and norms. Trust is reflected in cooperation and mutual assistance among members, social networks are formed through relationships with the community and external parties, and norms are manifested in adherence to traditional customs. In conclusion, social capital is a key factor in the success of the KOPSRI Community in preserving Bantengan art, both in terms of form and cultural values, so that it continues to exist amidst the current of modernization.
Validasi dan Finalisasi Ratna 2 Juli 2026
Keywords: Social Capital; Traditional Arts; Arts Preservation; KOPSRI; Bantengan Arts